Tinjauan Yuridis Pasal 75 Ayat (2) Undang Undang RI Nomor 36 Tahun 2009 Tentang Kesehatan Terhadap Dakwaan Jaksa Penuntut Umum Kepada Pelaku Pembunuhunan Anak Oleh Ibu Kandung (Studi Kasus Putusan Nomor 333 / PID.SUS/2021/ PN BKS) - Anisa Dwi Putri Barus; Achmad Zulfikar Siregar (Jurnal Sosial Politik dan Hukum, 2024)
Cases of child murder by biological mothers in Indonesia are still frequent and in the public spotlight. In the case study of Decision Number 333/PID. SUS/2021/PN BKS, a biological mother was charged with murdering her own 9-month-old biological child. In the indictment, the public prosecutor used Article 75 paragraph (2) of RI Law Number 36 of 2009 concerning Health as a legal basis to prosecute the perpetrator. The article emphasizes that anyone who violates health provisions that cause the death of others can be sentenced to prison. In the juridical review, Article 75 paragraph (2) of the Republic of Indonesia Law Number 36 of 2009 concerning Health is indeed relevant to cases of child murder by biological mothers. However, in this case, there are several weaknesses in the public prosecutor's indictment. First, there is no medical evidence to show that the child's health was completely disturbed due to his mother's acts of violence or negligence. Second, there is no strong evidence that the mother's acts of violence or negligence were intentional to kill her child. In an effort to prevent cases of child homicide by biological mothers in the future, the government also needs to increase public awareness about the importance of child health and protection. Education on how to raise children properly and properly and how to deal with stress in pregnant women or mothers with young children also needs to be improved. In addition, the government also needs to strengthen supervision of acts of violence or negligence against children to prevent cases of child murder by parents or guardians that are detrimental to the health and life of children.